Efektivitas Anti Bakteri Perasan Bawang Putih (Allium sativum L.) terhadap Pertumbuhan Staphylococcus aureus: The Effectiveness of Anti-Bacterial Juice of Garlic (Allium sativum L.) on the Growth of Staphylococcus aureus - Mardiyah, Siti (Universitas Muhammadiyah Sidoarjo, 2018)
Garlic has bioactive compounds that are efficacious as antibacterial (bacteriostatic) in some pathogenic bacteria, which one of them is Staphylococcus aureus. Major antimicrobial component is active on garlic especially allicin. The ability of garlic extract as anti-bacterial because of the combination of alisin and scordinin. Alisin serves as a natural antibiotic capable of killing antibiotic-resistant Staphylococcus aureus. This paper aims to study the effect of concentration of garlic juice on the growth of Staphylococcus aureus and determine the minimum concentration to prevent the growth of the bacteria. This type of research is experimental. The population and sample of this study were culture of pure Staphylococcus aureus grown on MSA medium (Manitol Salt Agar). Total sample of research are 28 samples. Staphylococcus aureus growth data were obtained by indirect observation through laboratory tests. Data analysis techniques used Kruskal-Wallis test with 5% error rate (0,05) and Mann Whitney test through SPSS 17,0 program. The result of anti bacterial test of garlic extract (Allium sativum Linn) with Kruskal-Wallis showed that there was influence of extract concentration of garlic on growth of Staphylococcus aureus (p = 0,000). While Mann - Whitney test results obtained that at 25% concentration is the minimum concentration that effectively prevent the growth of Staphylococcus aureus. Therefore it can be concluded that there is influence of extract of garlic juice on growth of Staphylococcus aureus.